Polycarbonate resin composition
A polycarbonate resin composition with specific amounts of organic sulfonic acid potassium salt and fluoropolymer addresses flame retardancy and thermal/moisture resistance issues, achieving 5VB level flame retardancy and improved stability.
Patent Information
- Application Number
- JP2023115380
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polycarbonate resins, particularly those using organic sulfonic acid metal salts, face challenges in achieving high flame retardancy beyond the 5VB level, and suffer from thermal deterioration and moisture resistance issues during molding and high-temperature applications.
A polycarbonate resin composition containing 0.001 to 0.5 parts by mass of an organic sulfonic acid potassium salt with a sodium ion content of 200 ppm to 1000 ppm and 0.001 to 1 part by mass of a fluoropolymer, specifically potassium perfluoromethanesulfonate, is formulated to enhance flame retardancy, thermal stability, and moisture resistance.
The composition achieves a high degree of flame retardancy at the 5VB level, exhibits excellent thermal stability during molding, and maintains superior heat and humidity resistance, addressing the limitations of traditional polycarbonate resins.
Smart Images

Figure 2025012506000001 
Figure 2025012506000002 
Figure 2025012506000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate resin composition, and more particularly to a polycarbonate resin composition having excellent flame retardancy, thermal stability and moist heat resistance, and a molded article thereof. [Background technology]
[0002] Polycarbonate resin has excellent mechanical properties such as impact resistance, as well as excellent heat resistance and transparency, and is therefore widely used in a wide range of applications, including electrical and electronic equipment parts, automotive interior and exterior parts, office equipment parts, various optical parts, machine parts, building materials, and sheets.
[0003] In recent years, high flame retardancy has been required for parts of electrical and electronic equipment, information terminal devices, etc., and in particular, in recent years, there is a growing demand to meet not only UL-94 V-0, but also a higher flame retardancy level of 5VB.
[0004] As a means for imparting flame retardancy to polycarbonate resins, halogen-based flame retardants have conventionally been used, but in recent years, phosphorus-based flame retardants and organic sulfonic acid metal salt-based flame retardants have come to be used. As the organic sulfonic acid metal salt, for example, a perfluoroalkylsulfonic acid metal salt compound (Patent Document 1) is used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 54-32456 Summary of the Invention [Problem to be solved by the invention]
[0006] However, although organic sulfonic acid metal salts exhibit excellent flame retardancy and are widely used, they are not sufficient to achieve 5VB level flame retardancy (all five test pieces burn within 60 seconds, and no cotton ignition due to dripping occurs). Furthermore, as a result of the inventor's investigation, it was found that the resin composition is prone to thermal degradation problems when it is retained during molding or when it is exposed to high temperatures such as 300°C, and further, there is also a problem that the moisture and heat resistance of the polycarbonate resin composition is prone to decrease. [Means for solving the problem]
[0007] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by a polycarbonate resin composition containing an organic sulfonate potassium salt having a sodium ion content within a specific range as the organic sulfonate potassium salt in combination with a fluoropolymer in specific amounts, and have thus completed the present invention. The present invention relates to the following polycarbonate resin composition and molded article.
[0008] 1. A polycarbonate resin composition comprising 100 parts by mass of polycarbonate resin (A), 0.001 to 0.5 parts by mass of an organic potassium sulfonate (B), and 0.001 to 1 part by mass of a fluoropolymer (C), wherein the sodium ion content of the organic potassium sulfonate (B) as measured by ion chromatography is 200 ppm or more and 1000 ppm or less. 2. The polycarbonate resin composition according to the above 1, wherein the organic sulfonate potassium salt (B) is a potassium perfluoroalkylsulfonate. 3. The polycarbonate resin composition according to the above 1, wherein the organic sulfonic acid potassium salt (B) is potassium perfluoromethanesulfonate. 4. The polycarbonate resin composition according to the above 1, wherein the organic sulfonic acid potassium salt (B) has a fluorine ion content of 200 ppm or more as measured by ion chromatography. 5. Pellets of the polycarbonate resin composition according to any one of 1 to 4 above. 6. A molded article obtained by molding the polycarbonate resin composition according to any one of 1 to 4 above. 7. A molded article obtained by molding the polycarbonate resin pellets described in 5 above. Effect of the Invention
[0009] The polycarbonate resin composition of the present invention has a high level of flame retardancy at the 5VB level, and is also excellent in thermal stability such as retention stability during molding, and further in moist heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the present invention will be described in detail with reference to embodiments and examples. In this specification, unless otherwise specified, the symbol "to" is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0011] The polycarbonate resin composition of the present invention is characterized in that it contains 0.001 to 0.5 parts by mass of an organic potassium sulfonate (B) and 0.001 to 1 part by mass of a fluoropolymer (C) per 100 parts by mass of a polycarbonate resin (A), and that the sodium ion content of the organic potassium sulfonate (B) measured by ion chromatography is 200 ppm or more and 1000 ppm or less.
[0012] [Polycarbonate resin (A)] The polycarbonate resin (A) used in the present invention is not particularly limited, and various types can be used. Polycarbonate resins can be classified into aromatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aromatic carbons, and aliphatic polycarbonate resins in which the carbons directly bonded to the carbonate bonds are aliphatic carbons, and either type can be used. Among them, aromatic polycarbonate resins are preferred as the polycarbonate resin (A) from the viewpoints of heat resistance, mechanical properties, electrical properties, etc.
[0013] Among the monomers that are raw materials for aromatic polycarbonate resins, examples of aromatic dihydroxy compounds include: Dihydroxybenzenes such as 1,2-dihydroxybenzene, 1,3-dihydroxybenzene (i.e., resorcinol), and 1,4-dihydroxybenzene; Dihydroxybiphenyls such as 2,5-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, and 4,4'-dihydroxybiphenyl;
[0014] dihydroxynaphthalenes such as 2,2'-dihydroxy-1,1'-binaphthyl, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene;
[0015] dihydroxydiaryl ethers such as 2,2'-dihydroxydiphenyl ether, 3,3'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 1,4-bis(3-hydroxyphenoxy)benzene, and 1,3-bis(4-hydroxyphenoxy)benzene;
[0016] 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-methoxy-4-hydroxyphenyl)propane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-cyclohexyl-4-hydroxyphenyl)propane, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene, bis(4-hydroxyphenyl)methane, Bis(4-hydroxyphenyl)cyclohexylmethane, Bis(4-hydroxyphenyl)phenylmethane, Bis(4-hydroxyphenyl)(4-propenylphenyl)methane, Bis(4-hydroxyphenyl)diphenylmethane, Bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-1-naphthylethan, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)hexane, 1,1-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)octane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)nonane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)dodecane, Bis(hydroxyaryl)alkanes such as;
[0017] 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,4-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,5-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-propyl-5-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-4-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-phenylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-phenylcyclohexane, Bis(hydroxyaryl)cycloalkanes such as;
[0018] 9,9-bis(4-hydroxyphenyl)fluorene, Cardo structure-containing bisphenols such as 9,9-bis(4-hydroxy-3-methylphenyl)fluorene;
[0019] 4,4'-dihydroxydiphenyl sulfide, Dihydroxydiaryl sulfides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide; Dihydroxydiaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide; 4,4'-dihydroxydiphenyl sulfone, dihydroxydiarylsulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenylsulfone; etc.
[0020] Of these, bis(hydroxyaryl)alkanes are preferred, and bis(4-hydroxyphenyl)alkanes are particularly preferred. In particular, from the standpoint of impact resistance and heat resistance, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A) and 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C) are preferred. The aromatic dihydroxy compounds may be used alone or in any combination of two or more in any ratio.
[0021] Among the monomers that are raw materials for polycarbonate resins, examples of carbonate precursors include carbonyl halides, carbonate esters, etc. The carbonate precursors may be used alone or in any combination and ratio of two or more.
[0022] Specific examples of carbonyl halides include phosgene; haloformates such as bischloroformates of dihydroxy compounds and monochloroformates of dihydroxy compounds; and the like.
[0023] Specific examples of carbonate esters include diaryl carbonates such as diphenyl carbonate and ditolyl carbonate; dialkyl carbonates such as dimethyl carbonate and diethyl carbonate; biscarbonates of dihydroxy compounds, monocarbonates of dihydroxy compounds, and carbonates of dihydroxy compounds such as cyclic carbonates.
[0024] The method for producing the polycarbonate resin (A) is not particularly limited, and any method can be adopted. Examples of the method include interfacial polymerization, melt transesterification, ring-opening polymerization of a cyclic carbonate compound, and solid-phase transesterification of a prepolymer. Among these, the interfacial polymerization and melt transesterification methods are preferred because they have a higher effect of improving resistance to moist heat, and the interfacial polymerization method is particularly preferred.
[0025] The molecular weight of the polycarbonate resin (A), expressed as a viscosity average molecular weight (Mv) calculated from the solution viscosity measured at 25° C. using methylene chloride as a solvent, is preferably 10,000 to 50,000, more preferably 11,000 to 40,000, of which 12,000 to 35,000, and particularly preferably 13,000 to 30,000. By setting the viscosity average molecular weight to the lower limit of the above range or more, the mechanical strength of the polycarbonate resin composition of the present invention can be further improved, and by setting the viscosity average molecular weight to the upper limit of the above range or less, the decrease in flowability of the polycarbonate resin composition of the present invention can be suppressed and improved, and molding processability can be improved to facilitate molding process. Two or more kinds of polycarbonate resins having different viscosity average molecular weights may be mixed and used. In this case, polycarbonate resins having a viscosity average molecular weight outside the above-mentioned preferable range may be mixed.
[0026] The viscosity average molecular weight [Mv] is calculated by using methylene chloride as a solvent, measuring the intrinsic viscosity [η] (unit: dl / g) at 25°C using an Ubbelohde viscometer, and calculating the viscosity average molecular weight [Mv] using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is the value calculated from the specific viscosity [η sp ] was measured and the value was calculated according to the following formula.
number
[0027] In order to improve the appearance and flowability of the molded article, the polycarbonate resin (A) may contain a polycarbonate oligomer. The viscosity average molecular weight [Mv] of this polycarbonate oligomer is usually 1500 or more, preferably 2000 or more, and usually 9500 or less, preferably 9000 or less. Furthermore, the amount of the polycarbonate oligomer contained is preferably 30% by mass or less of the polycarbonate resin (including the polycarbonate oligomer).
[0028] Furthermore, the polycarbonate resin (A) may be not only virgin raw materials but also polycarbonate resin regenerated from used products (so-called material recycled polycarbonate resin), and it is also preferable to contain both virgin raw materials and recycled resin, or it may be made of recycled polycarbonate resin. The proportion of recycled polycarbonate resin in the polycarbonate resin (A) is preferably 40% or more, 50% or more, 60% or more, or 80% or more, and it is also preferable that the recycled polycarbonate resin is 100%.
[0029] [Potassium organic sulfonate (B)] The polycarbonate resin composition of the present invention contains an organic sulfonic acid potassium salt (B). Preferable examples of the organic sulfonic acid potassium salt (B) include potassium salts of fluorinated aliphatic sulfonic acids or aromatic sulfonic acids.
[0030] The fluorine-containing aliphatic sulfonic acid is preferably potassium perfluoroalkylsulfonate, and examples of the alkyl group include methyl, ethyl, propyl, and butyl groups, and are preferably methyl, ethyl, and butyl groups, and are particularly preferably methyl and n-butyl groups. Among these, potassium salts of fluorine-containing aliphatic sulfonic acids having at least one C-F bond in the molecule, such as potassium perfluorobutanesulfonate and potassium trifluoromethanesulfonate, are preferred.
[0031] The aromatic sulfonic acid is preferably a potassium salt of benzenesulfonic acid or diphenylsulfonic acid, and the alkyl substitution on the benzene ring may be monoalkyl or dialkyl, but is preferably a monoalkyl-substituted product, and is preferably a monoalkylbenzenesulfonic acid potassium salt, and examples thereof include ortho, para, and meta products. Specific examples include dipotassium diphenylsulfone-3,3'-disulfonate, potassium diphenylsulfone-3-sulfonate, potassium benzenesulfonate, potassium (poly)styrenesulfonate, potassium paratoluenesulfonate, potassium (branched)dodecylbenzenesulfonate, and potassium trichlorobenzenesulfonate. Among these, potassium o-toluenesulfonate, potassium p-toluenesulfonate, and potassium m-toluenesulfonate are preferred.
[0032] Among the above-mentioned examples, potassium salts of fluorinated aliphatic sulfonic acids are preferred, potassium salts of perfluoroalkanesulfonic acids are more preferred, potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, etc. are more preferred, and potassium trifluoromethanesulfonate is particularly preferred.
[0033] The organic sulfonic acid potassium salt (B) may be used alone, or two or more different compounds may be used in any combination and in any ratio.
[0034] In the present invention, the organic sulfonic acid potassium salt (B) used has a sodium ion content of 200 ppm or more and 1000 ppm or less as measured by ion chromatography. The sodium ion content, in ppm by mass, in the organic sulfonic acid potassium salt (B) is preferably 200 ppm or more, more preferably 250 ppm or more, and is preferably 900 ppm or less, more preferably 700 ppm or less.
[0035] The production of an organic potassium sulfonate, for example potassium perfluoroalkylsulfonate, is usually carried out by a method of neutralizing a perfluoroalkylsulfonic acid with a basic compound such as potassium hydroxide. In this case, the remaining potassium hydroxide is difficult to remove by washing with lithium hydroxide, which is highly water-soluble, so it is washed and purified with an aqueous sodium hydroxide solution or ultrapure water, and then dried under reduced pressure to produce potassium perfluoroalkylsulfonate. The organic sulfonic acid potassium salt (B) used in the present invention can have a sodium ion content in the range of 200 to 1000 ppm by adjusting the amounts of sodium hydroxide, pure water, etc. in such a purification method. If there is a commercially available product with such a sodium ion content, it is also possible to select and use it.
[0036] The sodium ion concentration of the organic sulfonate potassium salt (B) is measured by dissolving a precisely weighed amount of the organic sulfonate potassium salt (B) sufficiently in ultrapure water (for reagents) and subjecting the solution to an ion chromatograph measuring device equipped with a cation column.
[0037] By using the organic sulfonic acid potassium salt (B) having a sodium ion content within the above range, it is possible to obtain a polycarbonate resin composition that has a high level of flame retardancy at the 5VB level, and is also excellent in thermal stability during heat retention and high-temperature molding, as well as in moist heat resistance.
[0038] Furthermore, the organic sulfonic acid potassium salt (B) preferably has a fluorine ion content measured by ion chromatography of 200 ppm (ppm by mass) or more, more preferably 220 ppm or more, and preferably 1200 ppm or less, more preferably 1100 ppm or less, and particularly preferably 1000 ppm or less.
[0039] The fluorine ion content of the potassium organic sulfonate can be adjusted, for example, by adjusting the amount of fluoride ions contained in the raw materials during production, the degree of removing hydrogen fluoride and the like obtained by the reaction, the degree of purification, etc. Also, it is possible to select and use a commercially available product having such a fluorine ion content.
[0040] The fluorine ion concentration of the organic sulfonate potassium salt (B) is measured by dissolving a precisely weighed amount of the organic sulfonate potassium salt (B) sufficiently in ultrapure water (for reagents) and subjecting the solution to an ion chromatograph measuring device equipped with an anion column.
[0041] The content of the organic potassium sulfonate (B) is 0.001 to 0.5 parts by mass relative to 100 parts by mass of the polycarbonate resin (A). A resin composition containing such an amount has high flame retardancy and excellent thermal stability during heat retention and high-temperature molding. The content of the organic potassium sulfonate (B) is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, 0.04 parts by mass or more, particularly preferably 0.05 parts by mass or more, and also preferably 0.4 parts by mass or less, more preferably 0.3 parts by mass or less, 0.2 parts by mass or less, 0.15 parts by mass or less, particularly preferably 0.1 parts by mass or less.
[0042] [Fluoropolymer (C)] The polycarbonate resin composition of the present invention contains the fluoropolymer (C) in an amount of 0.001 to 1 part by mass relative to 100 parts by mass of the polycarbonate resin (A). The fluoropolymer (C) may be used alone or in any combination of two or more in any ratio. By incorporating the fluoropolymer (C) in combination with the organic potassium sulfonate (B) in this manner, the melting properties of the resin composition can be improved, the drip prevention properties during combustion can be improved, and a high level of flame retardancy can be achieved. If the content of the fluoropolymer (C) is less than 0.001 parts by mass, the effect of improving flame retardancy becomes insufficient, and if it exceeds 1 part by mass, the molded product molded from the resin composition will have poor appearance and reduced mechanical strength. The content of the fluoropolymer (C) is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 0.15 parts by mass or more, particularly preferably 0.2 parts by mass or more, and is preferably 0.8 parts by mass or less, more preferably 0.6 parts by mass or less, and particularly preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A).
[0043] The fluoropolymer (C) is preferably a fluoroolefin resin. The fluoroolefin resin is usually a polymer or copolymer containing a fluoroethylene structure, and specific examples thereof include difluoroethylene resin, tetrafluoroethylene resin, and tetrafluoroethylene / hexafluoropropylene copolymer resin, with tetrafluoroethylene resin being preferred. In addition, the fluoropolymer is preferably one having fibril-forming ability, specifically, a fluoroolefin resin having fibril-forming ability can be mentioned. In this way, by having fibril-forming ability, there is a tendency that drip prevention property during combustion is significantly improved.
[0044] As the fluoroolefin resin having fibril-forming ability, a fluoroethylene resin having fibril-forming ability is preferable. Examples of commercially available aqueous dispersions of fluoroethylene resins include "Teflon (registered trademark) 6J" manufactured by Fluoro Products Co., Ltd., and "Polyflon F201L", "Polyflon F103", and "Polyflon FA500C" manufactured by Daikin Chemical Industries, Ltd. Furthermore, examples of commercially available aqueous dispersions of fluoroethylene resins include, for example, Mitsui Chemours Examples of such adhesives include "Teflon (registered trademark) 30J" and "Teflon (registered trademark) 31-JR" manufactured by Fluoro Products Co., Ltd., and "Fluon D-1" manufactured by Daikin Chemical Industries, Ltd. Furthermore, fluoroethylene polymers having a multilayer structure obtained by polymerizing vinyl monomers can also be used. Examples of such fluoroethylene polymers include polystyrene-fluoroethylene composites, polystyrene-acrylonitrile-fluoroethylene composites, polymethyl methacrylate-fluoroethylene composites, and polybutyl methacrylate-fluoroethylene composites, such as "Metablen A-3800" manufactured by Mitsubishi Chemical Corporation and "Brendex 449" manufactured by GE Specialty Chemicals.
[0045] The fluoropolymer (C) may be contained either as one type or as two or more types in any combination and ratio.
[0046] [Elastomer] The polycarbonate resin composition of the present invention also preferably contains an elastomer. As the elastomer, a graft rubber copolymer obtained by graft-copolymerizing a rubber component with a monomer component copolymerizable therewith is preferred. The method for producing such a graft rubber copolymer may be any of bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., and the copolymerization method may be one-stage grafting or multi-stage grafting.
[0047] The rubber component has a glass transition temperature of usually 0° C. or less, preferably −20° C. or less, and more preferably −30° C. or less. Specific examples of the rubber component include polybutadiene rubber, polyisoprene rubber, polyalkyl acrylate rubber such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymer, silicone rubber such as organopolysiloxane rubber, butadiene-acrylic composite rubber, IPN composite rubber consisting of organopolysiloxane rubber and polyalkyl acrylate rubber, styrene-butadiene rubber, ethylene-α-olefin rubber such as ethylene-propylene rubber, ethylene-butene rubber, and ethylene-octene rubber, ethylene-acrylic rubber, and fluororubber. These may be used alone or in combination of two or more. Among these, polybutadiene rubber, polyalkyl acrylate rubber, IPN type composite rubber consisting of organopolysiloxane rubber and polyalkyl acrylate rubber, and styrene-butadiene rubber are preferred from the standpoint of mechanical properties and surface appearance.
[0048] Specific examples of the monomer component that can be graft-copolymerized with the rubber component include aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, from the standpoint of mechanical properties and surface appearance, aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, and (meth)acrylic acid compounds are preferred, and (meth)acrylic acid ester compounds are more preferred. Specific examples of the (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate.
[0049] The elastomer is preferably a core / shell type graft copolymer type in terms of impact resistance and surface appearance. Among them, a core / shell type graft copolymer is preferred, which is composed of at least one rubber component selected from polybutadiene-containing rubber, polybutyl acrylate-containing rubber, and IPN-type composite rubber composed of organopolysiloxane rubber and polyalkyl acrylate rubber as a core layer, and a shell layer formed by copolymerizing (meth)acrylic acid ester around the core layer, and in particular, a core / shell type elastomer having a butadiene-based rubber as a core is preferred. In the above-mentioned core / shell type graft copolymer, one containing 40% by mass or more of the rubber component is preferred, and one containing 60% by mass or more is more preferred. Also, one containing 10% by mass or more of the (meth)acrylic acid component is preferred.
[0050] Preferable specific examples of these core / shell type graft copolymers include methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic-butadiene rubber copolymer, methyl methacrylate-acrylic-butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic-silicone IPN rubber) copolymer, etc. Such rubbery polymers may be used alone or in combination of two or more.
[0051] When the polycarbonate resin composition of the present invention contains an elastomer, the content thereof is preferably 0.01 to 10 parts by mass, particularly 1 to 10 parts by mass, and even more preferably 2 to 8 parts by mass, per 100 parts by mass of the polycarbonate resin (A).
[0052] [Stabilizer] The polycarbonate resin composition of the present invention preferably contains a stabilizer, and the stabilizer is preferably a phosphorus-based stabilizer or a phenol-based stabilizer.
[0053] Any known phosphorus stabilizer can be used as the phosphorus stabilizer. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.
[0054] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Examples of such organic phosphite compounds include "ADK STAB 1178", "ADK STAB 2112", and "ADK STAB HP-10" manufactured by ADEKA CORPORATION, "JP-351", "JP-360", and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS 168" manufactured by BASF. The phosphorus-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.
[0055] The content of the phosphorus-based stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and usually 1 part by mass or less, preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the phosphorus-based stabilizer is less than the lower limit of the above range, the thermal stabilization effect may be insufficient, and if the content of the phosphorus-based stabilizer is more than the upper limit of the above range, the effect may plateau and become uneconomical.
[0056] The phenol-based stabilizer includes, for example, a hindered phenol-based antioxidant. Specific examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6- triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.
[0057] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred.Specific examples of such phenol-based antioxidants include "Irganox 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA. The phenol-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.
[0058] The content of the phenolic stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). By making the content of the phenolic stabilizer equal to or more than the lower limit of the above range, the effect as a phenolic stabilizer can be sufficiently obtained. In addition, by making the content of the phenolic stabilizer equal to or less than the upper limit of the above range, the effect does not plateau, and it is economical.
[0059] [Ultraviolet absorber] The polycarbonate resin composition of the present invention also preferably contains an ultraviolet absorber. Examples of the ultraviolet absorbing agent include inorganic ultraviolet absorbing agents such as cerium oxide and zinc oxide; and organic ultraviolet absorbing agents such as benzotriazole compounds, benzophenone compounds, salicylate compounds, cyanoacrylate compounds, triazine compounds, oxalilide compounds, malonic acid ester compounds, and hindered amine compounds. Among these, organic ultraviolet absorbing agents are preferred, and benzotriazole compounds are more preferred. By selecting an organic ultraviolet absorbing agent, the transparency and mechanical properties of the resin composition of the present invention can be improved.
[0060] Specific examples of the benzotriazole compound include, for example, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-5-chlorobenzotriazole. t-amyl)-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] and the like. Among these, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] are preferred, and 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole is particularly preferred.
[0061] Specific examples of the benzophenone compound include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-n-dodecyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone.
[0062] Specific examples of the salicylate compound include phenyl salicylate, 4-tert-butylphenyl salicylate, and the like. Specific examples of the cyanoacrylate compound include ethyl-2-cyano-3,3-diphenylacrylate, 2-ethylhexyl-2-cyano-3,3-diphenylacrylate, and the like. Specific examples of oxanilide compounds include 2-ethoxy-2'-ethyloxalinic acid bis-arylide and the like. As the malonic acid ester compound, 2-(alkylidene)malonic acid esters are preferred, and 2-(1-arylalkylidene)malonic acid esters are more preferred.
[0063] The content of the ultraviolet absorber, when contained, is usually 0.05 parts by mass or more, preferably 0.1 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the polycarbonate resin (A). If the content of the ultraviolet absorber is less than the lower limit of the above range, the effect of improving weather resistance and light resistance may be insufficient, and if the content of the ultraviolet absorber is more than the upper limit of the above range, mold deposits or the like may occur, causing mold contamination. The ultraviolet absorbing agent may be contained alone or in any combination and ratio of two or more kinds.
[0064] [Release agent] The polycarbonate resin composition of the present invention preferably contains a mold release agent (lubricant). Examples of the mold release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, and polysiloxane-based silicone oils.
[0065] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.
[0066] The aliphatic carboxylic acid in the ester of aliphatic carboxylic acid and alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term aliphatic is used to include alicyclic compounds.
[0067] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.
[0068] The above ester may contain an aliphatic carboxylic acid and / or alcohol as an impurity. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be one type, or two or more types may be used in any combination and ratio.
[0069] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.
[0070] Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone.
[0071] The above-mentioned release agents may be contained alone or in any combination and ratio of two or more kinds.
[0072] The content of the release agent is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, based on 100 parts by mass of the polycarbonate resin (A). By making the content of the release agent equal to or more than the lower limit of the above range, it becomes easier to obtain a sufficient effect of releasability, and by making the content of the release agent equal to or less than the upper limit of the above range, it becomes easier to prevent mold contamination during injection molding.
[0073] [Additives, etc.] The polycarbonate resin composition of the present invention may contain additives other than those described above, such as flame retardants other than the organic sulfonic acid potassium salt (B), fluorescent brighteners, pigments, dyes, plasticizers, compatibilizers, etc. These additives may be contained alone or in combination of two or more.
[0074] In addition, the polycarbonate resin (A) may contain other resins. Examples of other resins include thermoplastic polyester resins such as polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate; styrene-based resins such as polystyrene resin, high impact polystyrene resin (HIPS), and acrylonitrile-styrene copolymer (AS resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resin; polyimide resin; polyetherimide resin; polyurethane resin; polyphenylene ether resin; polyphenylene sulfide resin; polysulfone resin; and polymethacrylate resin. When a resin other than the polycarbonate resin (A) is contained, the content thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, per 100 parts by mass of the polycarbonate resin (A).
[0075] [Polycarbonate resin composition] The polycarbonate resin composition of the present invention has a high level of flame retardancy, and is capable of achieving 5VB in the UL-94 5V test using a UL test piece having a thickness of 3.0 mm.
[0076] The polycarbonate resin composition is molded into a molded article. The manufacturing method of the molded product can be any molding method generally used for polycarbonate resin compositions. Examples of such methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, and the like. Also, molding using a hot runner system can be used. Among them, injection molding methods such as injection molding, ultra-high speed injection molding, and injection compression molding are preferred.
[0077] [Molded products] Examples of molded articles include parts for electric / electronic devices, office automation equipment, information terminal devices, machine parts, home appliances, vehicle parts, building materials, various containers, leisure goods / miscellaneous goods, lighting equipment, etc. Among them, the molded articles are suitable for use in parts for electric / electronic devices, office automation equipment, information terminal devices, home appliances, lighting equipment, etc., and are suitable for use in, for example, components for secondary battery devices used indoors or outdoors, battery packs, storage batteries for electric bicycles, etc., and components for casings used outdoors, etc. EXAMPLES
[0078] The present invention will be described in more detail below with reference to examples, but the present invention should not be construed as being limited to the following examples. The components used in the examples and comparative examples are as shown in Table 1 below.
[0079] [Table 1]
[0080] Potassium perfluoromethanesulfonates B1 to B6 were produced by changing the amount of sodium hydroxide solution used when the potassium hydroxide and hydrogen fluoride remaining in the above-mentioned production process were washed and purified with sodium hydroxide solution, and by changing the number of washings performed with ultrapure water when washing and purifying the potassium hydroxide and hydrogen fluoride remaining in the above-mentioned production process. If the amount of sodium hydroxide is large, the amount of sodium ions will be large and the amount of fluorine ions will be small. On the other hand, if the amount of sodium hydroxide is small, the amount of sodium ions will be small and the amount of fluorine ions will be large. Furthermore, if the number of washings with ultrapure water is small, the amount of sodium ions will also be large. The amounts of sodium ions and fluorine ions were measured by ion chromatography using the following apparatus and conditions. 0.1 g of the sample was taken, diluted to 20 mL with ultrapure water, and then subjected to an ion chromatograph "INTEGRATION" manufactured by Thermo Fisher Scientific. For the column, a cation column CS16 was used for sodium ions and an anion column AS18 was used for fluoride ions. The calibration curves were prepared at four points each in the ranges of 0.03 mg / L to 1.0 mg / L for sodium ions and 0.025 mg / L to 1.0 mg / L for fluoride ions.
[0081] (Examples 1 - 6, Comparative Examples 1 - 11) <Manufacture of Resin Composition Pellets> The above - mentioned respective components were blended at the ratios (parts by mass) shown in Table 4 below, mixed in a tumbler for 20 minutes, and then supplied to a twin - screw extruder "TEX30α" manufactured by Japan Steel Works, Ltd. equipped with 1 vent. Kneading was carried out under the conditions of a screw rotation speed of 200 rpm, a discharge rate of 30 kg / hr, and a barrel temperature of 280°C. The molten resin extruded in a strand shape was rapidly cooled in a water tank and pelletized using a pelletizer to obtain pellets of the polycarbonate resin composition.
[0082] <Preparation of Test Specimens> After drying the pellets obtained by the above - mentioned manufacturing method at 120°C for 4 hours, injection molding was carried out using an SE100DU - type injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. under the conditions of a cylinder temperature of 260°C, a mold temperature of 80°C, and a molding cycle of 30 seconds. Test specimens for UL94 - V with a length of 125 mm, a width of 13 mm, and a thickness of 1.5 mm, and test specimens for UL94 - 5VB with a thickness of 3.0 mm were injection - molded.
[0083] <Flame Retardancy Evaluation> The flame retardancy of each polycarbonate resin composition was evaluated by conditioning the UL combustion test specimens obtained by the above - mentioned method in a thermo - hygrostat chamber at a temperature of 23°C and a humidity of 50% for 48 hours, and then conducting the test in accordance with the UL94 test (combustion test for plastic materials used in parts of equipment) defined by UL in the United States.
[0084] <UL94 - V Test> The UL94-V test is a method for evaluating flame retardancy based on the afterflame time and dripping properties after a burner flame is applied to the bottom end of a test specimen held vertically for 10 seconds. In order to achieve flame retardancy of V-0, V-1, or V-2, the standards shown in Table 2 below must be met.
[0085] [Table 2]
[0086] Here, the afterflame time is the length of time that the test specimen continues to burn with a flame after the ignition source is removed. Also, cotton ignition by dripping is determined by whether or not the cotton used for marking, located about 300 mm below the bottom end of the test specimen, is ignited by dripping material from the test specimen. Furthermore, if even one of the five tests for one material does not meet the above criteria, it is deemed not to have met V-2 and is rated NR (not rated). rated).
[0087] <ul94-5vb> In the UL94-5V test, a test specimen is held vertically and a burner flame is applied to the corner of the specimen at an angle of 20 degrees from the vertical for 5 seconds, then removed for 5 seconds. This cycle is repeated 5 times, after which the flame is evaluated based on the after-flame time and dripping properties. In order to have 5VB flame resistance, it is necessary to satisfy the standards shown in Table 3 below.
[0088] [Table 3]
[0089] Here, the afterflame time is the length of time that the test specimen continues to burn with a flame after the fifth contact with the flame. Cotton ignition by dripping is determined by whether or not the cotton used for marking, located approximately 300 mm below the bottom end of the test specimen, is ignited by dripping material from the test specimen. Furthermore, if any of the five tests for one material do not meet the above criteria, it is rated as NR (not rated). rated).
[0090] [Liquidity (Q value, unit: x 10 -2 cm 3 / sec)] The fluidity (flow value: Q value) of each polycarbonate resin composition was evaluated by drying the pellets obtained by the above-mentioned manufacturing method at 120°C for 4 hours, and then measuring the fluidity (flow value: Q value) using a constant test force extrusion capillary rheometer "CFT-500D" manufactured by Shimadzu Corporation under the conditions of a cylinder temperature of 300°C, a test force of 160 kgf, and a melting time of 7 minutes. The Q value measured under these conditions is referred to as "Q value (300°C, no retention)" in the table below.
[0091] [Retention thermal stability] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours, and then the Q value was measured using a Shimadzu Corporation constant test force extrusion capillary rheometer "CFT-500D" under the conditions of a cylinder temperature of 300°C, a test force of 160 kgf, and a melting time of 17 minutes. The Q value measured under these conditions is referred to as "Q value (300°C, 10 minutes residence)" in the table below. The difference ΔQ between the two Q values was calculated using the following formula, and used as an index of residence thermal stability. ΔQ value (retention) = Q value (300℃, 10 min. retention) - Q value (300℃, no retention) The ΔQ value (retention) represents the change in fluidity of the resin due to thermal retention deterioration, and a smaller value is preferable since it indicates superior thermal retention stability.
[0092] [Moisture and heat resistance] The pellets obtained by the above-mentioned manufacturing method were dried at 120°C for 4 hours, and then the Q value was measured using a Shimadzu constant test force extrusion capillary rheometer "CFT-500D" under the conditions of a cylinder temperature of 280°C, a test force of 160 kgf, and a melting time of 7 minutes. The measured Q value is shown in the table below as "Q value (280°C, no PCT treatment)". The pellets obtained by the above manufacturing method were subjected to 100 hours of treatment in a water vapor atmosphere at 121°C, 0.1MPa pressure, and 100% humidity using a highly accelerated life tester "EHS-221M" manufactured by ESPEC, and the Q value was measured in the same manner as above. The measured Q value is referred to as "Q value (280°C, PCT treatment)" in the table below. The difference between the Q values, ΔQ, was calculated using the following formula and used as an index of moist heat resistance. ΔQ value (PCT) = Q value (280℃, PCT treatment) - Q value (280℃, no PCT treatment) The ΔQ value (PCT) indicates the change in the fluidity of the resin due to deterioration in a humid and hot environment, and a smaller value is preferable because it indicates excellent resistance to humid and hot environments.
[0093] The above evaluation results are shown in Tables 4 to 6 below. [Table 4]
[0094] [Table 5]
[0095] [Table 6] [Industrial Applicability]
[0096] INDUSTRIAL APPLICABILITY The polycarbonate resin composition of the present invention has an extremely high level of flame retardancy, is excellent in thermal stability against retention during molding, and is also excellent in resistance to moist heat, and therefore can be suitably used for various molded products.
Claims
1. A polycarbonate resin composition comprising 0.001 to 0.5 parts by mass of an organic potassium sulfonate (B) and 0.001 to 1 part by mass of a fluoropolymer (C) per 100 parts by mass of a polycarbonate resin (A), wherein the sodium ion content of the organic potassium sulfonate (B) is 200 ppm or more and 1000 ppm or less as measured by ion chromatography.
2. 2. The polycarbonate resin composition according to claim 1, wherein the organic potassium sulfonate (B) is a potassium perfluoroalkylsulfonate.
3. 2. The polycarbonate resin composition according to claim 1, wherein the organic potassium sulfonate (B) is potassium perfluoromethanesulfonate.
4. 2. The polycarbonate resin composition according to claim 1, wherein the organic sulfonic acid potassium salt (B) has a fluorine ion content of 200 ppm or more as measured by ion chromatography.
5. A pellet of the polycarbonate resin composition according to any one of claims 1 to 4.
6. A molded article obtained by molding the polycarbonate resin composition according to any one of claims 1 to 4.
7. A molded article obtained by molding the polycarbonate resin pellets according to claim 5.
Citation Information
Patent Citations
Preparation of jasmonic acid analogue
JP1979032456A